Experience Report about the Participation of Researchers of the Federal University of Rio Grande do Sul on the Internet Engineering Task Force - Nobre, Jéferson; Granville, Lisandro (Anais do Workshop Pré-IETF (WPIETF); 2015: Anais do II Workshop Pré-IETFDO - 10.5753/wpietf.2015.10469, 2015)
The present work is an experience report about the participation of the authors, a Professor and a Ph.D Student of Federal University of Rio Grande do Sul, on the Internet Engineering Task Force. Such participation is funded by the Public Call 0001/2014 of the CGI.br.